On the role of interactions in trans-sonically flowing atomic condensates(a)Contribution to the Focus Issue Turbulent Regimes in Bose-Einstein Condensates edited by Alessandra Lanotte, Iacopo Carusotto and Alberto Bramati. (22nd March 2021) - Tettamanti, M.; Carusotto, I.; Parola, A.
Abstract: We provide a joint numerical-analytical study of the physics of a flowing atomic Bose-Einstein condensate in the combined presence of an external trap and a step potential which accelerates the atoms out of the condensate creating a pair of neighbouring black- and white-hole horizons. In particular, we focus on the rapidly growing density modulation pattern that appears in the supersonic region, an experimentally observed feature that was related to black-hole lasing phenomena. A direct assessment of the role of interactions in this process suggests an interpretation of the experimental data in terms of linear interference of atomic waves rather than collective effects. Our conclusions are further supported by an analytical solution of the Schrödinger equation in terms of Airy wave functions.